A pilot trial of collaborative care with motivational interviewing to reduce opioid risk and improve chronic pain management. (27th January 2021) - Borsari, Brian; Li, Yongmei; Tighe, Jennifer; Manuel, Jennifer K.; Gökbayrak, N. Simay; Delucchi, Kevin; Morasco, Benjamin J.; Abadjian, Linda; Cohen, Beth E.; Baxley, Catherine; Seal, Karen H.
Abstract: Background and Aims: Opioid use and chronic pain are prevalent in the veteran population. Collaborative care enhances coordination between patients and their care teams, and motivational interviewing (MI) is a communication style designed to facilitate behavior change. This study evaluated the use of collaborative care with MI (CCMI) with patients with chronic pain and high‐risk prescription opioid use. Design: Small pilot study of a randomized controlled trial. Setting: An urban Veterans Affairs (VA) Medical Center in the United States. Participants: One hundred adult veterans with chronic pain currently enrolled into primary care and receiving long‐term opioid therapy. Intervention and Comparator: During an initial 1‐hour visit with a study primary‐care physician (PCP), all veterans ( n = 100) developed a personalized pain care plan, after which they were randomized to receive four sessions (at 4, 6, 8 and 12 weeks) of either CCMI ( n = 51) or attention control psychoeducation (ACP; n = 49). Subsequently, participants had 30‐minute follow‐up visits with study PCPs and post‐treatment assessment at 12 weeks. Measurements: Co‐primary outcomes measures assessed opioid risk and pain interference; secondary measures assessed pain severity, PCP rating of opioid risk and pain management goals. Findings: At 12 weeks, intent‐to‐treat (ITT) analyses using multivariate mixed‐effects linear regression were inconclusive regarding the between‐group differences in primary and secondary outcomes at post‐intervention (12 weeks). Bayes factors for opioid risk, pain interference, pain severity and PCP ratings were 1.96, 1.36, 0.45 and 0.82, respectively. Veterans in the CCMI group reported implementing more complementary integrative health (CIH) goals (e.g. yoga) than did those in the ACP group ( d = 0.54). Conclusions: US veterans with chronic pain who received collaborative care with motivational interviewing reduced their high‐risk opioid use and showed improved pain interference and severity after an intake with a primary‐care provider involving shared decision‐making and the creation of a personalized pain care plan.